2020
DOI: 10.3390/nu12020483
|View full text |Cite
|
Sign up to set email alerts
|

Beneficial Effects of Dark Chocolate for Episodic Memory in Healthy Young Adults: A Parallel-Groups Acute Intervention with a White Chocolate Control

Abstract: There is good evidence that cocoa flavonoids can acutely improve cognitive function in humans, possibly via mechanisms such as increased cerebral blood flow. To date, much of the evidence is based on measures of executive function with extracts and cocoa-based interventions with a high flavonoid content. The aim of the present study was to explore whether benefits to episodic verbal memory and mood are observed two hours post consumption of a commercially available dark chocolate (DC) bar relative to a 35 g wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 35 publications
0
19
0
1
Order By: Relevance
“…In the other three studies, even if the cocoa or chocolate source of polyphenols was consumed for 5 days in the case of Francis et al (2006) [33], for 9 to 24 days in the case of Calderon-Garciduenas et al (2013) [37], and for 28 days in that of Massee et al (2015) [38], in all three the endpoints were measured between 1.5 and 4 h after the last ingestion of the CF source. Regarding the amount of chocolate or cocoa consumed by participants in the different studies, it ranges from 35 mg of epicatechin contained in 24 gr 70% cocoa chocolate [36] or 85 mg total flavanols contained in 35 gr 70% cocoa chocolate [43] to almost 1 gr CF [39].…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…In the other three studies, even if the cocoa or chocolate source of polyphenols was consumed for 5 days in the case of Francis et al (2006) [33], for 9 to 24 days in the case of Calderon-Garciduenas et al (2013) [37], and for 28 days in that of Massee et al (2015) [38], in all three the endpoints were measured between 1.5 and 4 h after the last ingestion of the CF source. Regarding the amount of chocolate or cocoa consumed by participants in the different studies, it ranges from 35 mg of epicatechin contained in 24 gr 70% cocoa chocolate [36] or 85 mg total flavanols contained in 35 gr 70% cocoa chocolate [43] to almost 1 gr CF [39].…”
Section: Methodological Aspectsmentioning
confidence: 99%
“…It was suggested that further investigation was needed of acute cognitive effects of chocolate along with examination of functional brain changes associated with cocoa-flavanols [ 54 ]. Recent human trials have shown that dark chocolate (35 g) improved verbal memory in health young adults, which further supports exploration in this area [ 12 ]. In addition to their effects on memory, functional and all rounded assessments utilising physiological and cognitive challenge tasks are also important factors to consider when evaluating the effects of cocoa-flavanol intake on brain function [ 55 ].…”
Section: Discussionmentioning
confidence: 69%
“…Several meta-analyses have suggested the benefits of chocolate consumption in reducing the risk of cardiometabolic events including coronary heart disease, myocardial infarction, stroke, and diabetes [ 9 , 10 ]. Apart from potential health promoting cardiometabolic effects, chocolate consumption has also been reported to improve cognition in clinical trials [ 11 , 12 ], supported by preclinical studies [ 13 , 14 ]. The cognitive benefits of chocolate are further supported by a recent systematic review which reported improvement in cognitive scores or task performance among young adults (less than 25 years old) and children with chronic chocolate consumption, again possibly attributed to polyphenols, including flavanols [ 15 ].…”
Section: Introductionmentioning
confidence: 99%
“…Cocoa flavonoids or dark chocolate (≥70% cocoa) intake also contribute to cognitive performance. Several clinical studies demonstrated that cocoa intake can improve neurovascular coupling, increase regional glucose metabolism in the occipital and visual cortex, and enhance normal cognitive functioning [ 249 , 250 , 251 , 252 ]. Moreover, a retrospective cohort study that included 55 patients diagnosed with amnestic mild cognitive impairment reported that cocoa flavonoids appear to decrease the progression of mild cognitive impairment to dementia [ 253 ].…”
Section: Prevention Of Cognitive Decline Through Nutritional Interventionsmentioning
confidence: 99%